Numerical investigation of fluid flow and heat transfer in rough microchannel - Abdollahi, Ayoub (2013)
In this study an incompressible 2-D Navier Stokes solver is used to study the effects of surface roughness in microchannel flows numerically. An internally roughened microchannel is generated by selecting a set of triangular shaped peak as roughness with different range from 0.00 % to 8%. Water is taken as working fluid with constant properties. A two dimensional rough rectangular microchannel is modelled by GAMBIT. For specific boundary condition, the geometry is solved in the Computational Fluid Dynamics, CFD software namely FLUENT. Besides SIMPLE method in FLUENT is used for solving the governing equations. This work focused on the effect of surface roughness on pressure drop and heat transfer behaviour in the microchannel. It was obtained that surface roughness and Reynolds number have an important role on friction factor, Poiseuille number and heat transfer. Poiseuille number and friction factor increased significantly by enhancing relative roughness. Besides, the laminar heat transfer in microchannels is also enhanced by roughness increases. Moreover, the roughness has significant effects on performances of microchannel.